Cholestatic Jaundice in Infants An Experience in Tertiary Care Hospital (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Background: Neonatal cholestasis is defined as prolonged elevation of serum levels of conjugated bilirubin beyond the first 14 days of life. Cholestasis in a newborn can be due to infectious, genetic, metabolic, or undefined abnormalities giving rise to mechanical obstruction of bile flow or to functional impairment of hepatic excretory function and bile secretion. Early detection and timely accurate diagnosis are important for successful treatment and a favorable prognosis. Objective: The present study has been designed to determine the etiology of cholestatic jaundice in infants along with their clinical profile. Methodology: This cross-sectional study was conducted from August 2010 through January 2011 in the Paediatric Gastroenterology & Nutrition Department, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. For the study purpose 40 consecutive cases of cholestatic jaundice were included who fulfilled the inclusion criteria. Result: Biliary atresia was the commonest (42.5%) cause of cholestatic jaundice followed by neonatal hepatitis/ idiopathic neonatal hepatitis. Other causes of cholestatic of the infants were term and of normal birth weight in cases of biliary atresia (BA) but in NH/INH group significant number of infants were preterm and of low birth weight. Mean age at onset of jaundice was 10.1 ± 4.18 days, and mean age at presentation was 113.7 ±15.38 days. In cases of BA Jaundice, intermittent / persistent pale stool, dark urine was found in all cases and hepatomegaly and splenomegaly were found in 88.2% and 64.8% of cases respectively. Ultrasonographically in most of the cases of BA gallbladder was found either small in size or absent or bile ducts were not visualized. In cases of NH/INH visualization of normal gallbladder while fasting and contraction was observed after meal. Histologically typical features BA were found in 12 out of 17 cases of BA and features of early biliary cirrhosis in 4 infants and 10 patients showed features of INH. Conclusion: Biliary atresia was found to be the commonest cause of neonatal cholestasis in the present study. DOI: http://dx.doi.org/10.3329/jbcps.v32i1.21029 J Bangladesh Coll Phys Surg 2014; 32: 9-15